2013
DOI: 10.3389/fcimb.2013.00072
|View full text |Cite
|
Sign up to set email alerts
|

Engineering production of functional scFv antibody in E. coli by co-expressing the molecule chaperone Skp

Abstract: Single-chain variable fragment (scFv) is a class of engineered antibodies generated by the fusion of the heavy (VH) and light chains (VL) of immunoglobulins through a short polypeptide linker. ScFv play a critical role in therapy and diagnosis of human diseases, and may in fact also be developed into a potential diagnostic and/or therapeutic agent. However, the fact that current scFv antibodies have poor stability, low solubility, and affinity, seriously limits their diagnostic and clinical implication. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 42 publications
3
42
0
1
Order By: Relevance
“…We thought it likely that some periplasmic factor must be assisting LacZ folding. Because previous studies have implicated the periplasmic chaperones skp and fkpA in the folding of heterologous proteins (23)(24)(25)(26)(27)(28)(29), we chose to see what effect disruption of these genes might have on the ␤-galactosidase activity of a strain expressing the malF-lacZ102 fusion in the absence of DsbA. While disruption of skp did not decrease ␤-galactosidase activity, we found that disruption of fkpA reduced it by a factor of 2.6 (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…We thought it likely that some periplasmic factor must be assisting LacZ folding. Because previous studies have implicated the periplasmic chaperones skp and fkpA in the folding of heterologous proteins (23)(24)(25)(26)(27)(28)(29), we chose to see what effect disruption of these genes might have on the ␤-galactosidase activity of a strain expressing the malF-lacZ102 fusion in the absence of DsbA. While disruption of skp did not decrease ␤-galactosidase activity, we found that disruption of fkpA reduced it by a factor of 2.6 (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Over the past several decades, a variety of methods for producing a stable, soluble, and higher-affinity scFv antibody have been developed, including coexpression with molecular chaperons (3,31), expression in different host systems (32), genetic fusion to specific proteins (33), and GFP-based binders (29,30). Perhaps the most effectively used method is the use of a new type of antibody based on a GFP scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…T o date, antibodies are used for a very broad and still steadily expanding spectrum of applications, such as cancer therapy, disease diagnosis, and signal pathway investigation (1)(2)(3). Monoclonal antibodies (Abs) produced by hybridoma technology have been widely used to rapidly detect pathogens in food and raw seafood (4).…”
mentioning
confidence: 99%
See 2 more Smart Citations